Fungi from the “Lost World”: Novel Asterinaceae from the Ricardo Franco Hills (Brazil), with a worldwide key to Lembosia species on Melastomataceae - Firmino, André Luiz; Vélez-Zambrano, Sergio Miguel; Barreto3, Robert Weingart; Dianese, Jose Carmine (Phytotaxa, 2019)
A pioneering search for fungi was carried out at the remote and iconic region of the Ricardo Franco Hills (State of Mato Grosso, Brazil) at the Bolivian border, known in the popular literature as “the lost world”. Here, four new species of the Asterinaceae on various hosts are documented: Asterina cerradensis sp. nov. on Davilla elliptica (Dilleniaceae), Asterina malvacearum sp. nov. on Sida rhombifolia (Malvaceae), A. indecora newly recorded from Brazil on Heteropterys nervosa (Malpighiaceae), Lembosia matogrossensis sp. nov. on Miconia prasina (Melastomataceae), and L. miconiphylla sp. nov. on Miconia nervosa (Melastomataceae). A worldwide key to Lembosia spp. occurring on Melastomataceae is included.